Epidemiologic Profile of Ischemic Stroke Patients with Dyslipidemia in Dr. Soetomo General Academic Hospital Patient - Prakoso, Raditya Ardra Putra; Ardhi, Mohammad Saiful; Thamrin, Husin; Setyowatie, Sita (Universitas Airlangga, 2025)
Highlight: This study provides insights into the epidemiologic profile of ischemic stroke patients with dyslipidemia in Dr. Soetomo General Academic Hospital. The majority of patients had hypertension, the most common comorbidity with low HDL-C levels Most patients showed moderate stroke severity and high levels of consciousness, with a majority proportion demonstrating recovery. ABSTRACT Introduction: Ischemic stroke is a major medical issue, especially in individuals with dyslipidemia, as it can elevate both the likelihood and severity of stroke incidents. This study is essential due to the rising prevalence of stroke and limited data regarding ischemic stroke patients with dyslipidemia in Indonesia. Understanding these traits is important for enhancing preventative and treatment strategies. Objective: This study intended to assess the epidemiologic profile of ischemic stroke patients with dyslipidemia in a tertiary hospital in Indonesia. Methods: This descriptive study assessed 116 medical records of ischemic stroke patients with dyslipidemia admitted to Dr. Soetomo General Academic Hospital in Surabaya, Indonesia, from January to June 2023. The collected data encompassed demographics, comorbidities, lipid profiles, and clinical outcomes. Dyslipidemia was defined based on the PERKENI guidelines, and stroke severity was assessed using the GCS and NIHSS scales. Results: The majority of ischemic stroke patients with dyslipidemia (77.6%) had low HDL-C levels. There were 64 males and 52 females; most of them were between the ages of 56 and 65. Hypertension was the most common comorbidity (64.7%), followed by diabetes (39.7%), heart disease (12.9%), and obesity (11.2%). Of 40 NIHSS-assessed patients, 26 had moderate, 8 mild, 2 moderate-to-severe, and 4 severe strokes. The majority of patients (70.7%) recovered. Conclusion:The majority of dyslipidemia-related ischemic stroke patients, aged 56 to 65, had low HDL-C levels. Hypertension was the main comorbidity, with many experiencing their first stroke. Most patients had high consciousness, moderate stroke severity, and showed improvements.